Sorption of Pb(II) and Cu(II) on the colloid of black soil, red soil and fine powder kaolinite: effects of pH, ionic strength and organic matter. Issue 1 (1st January 2019) - Liu, Yuting; Xu, Zhao; Hu, Xin; Zhang, Nan; Chen, Ting; Ding, Zhuhong
ABSTRACT: The sorption potentials of two soil colloids and fine powder kaolinite for Pb(II) and Cu(II) were analyzed, and the effects of pH, ionic strength and organic matter on the sorption were invetigated. The two soil colloids and fine powder kaolinite were characterized by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) analysis. Black soil had more mineral compositions and surface functional groups. The sorption was pH-dependent. In the presence of humic acid, the adsorption of Pb(II) and Cu(II) ions on soil was increased, while the increase in ionic strengths decreased the adsorption. Sorption kinetics and isotherms of Pb(II) and Cu(II) onto three soil colloids were well fitted with Pseudo-second-order model and Langmuir model/Freundlich model. Black soil had the highest sorption capacity of Pb(II) (44.287 mg g −1 ) and Cu(II) (11.109 mg g −1 ), followed by red soil (9.764 and 4.152 mg g −1 ) and kaolinite (7.612 and 3.064 mg g −1 ). The two metals competed with each other during sorption.